South asian folklore in tcfransition : crafting new horizons - Korom, Frank J.; Korom Frank J; Lowthorp Leah K (London : Routledge, 2019)
"The Indian Subcontinent has been at the centre of folklore inquiry since the 19th century, yet, while much attention was paid to India by early scholars, folkloristic interest in the region waned over time until it virtually disappeared from the research agendas of scholars working in the discipline of folklore and folklife.
1. Historicizing folklore 2. Materializing folklore 3. Politicizing folklore.
Includes index
Keywords: Asian History; Asian culture